Aktivisme Digital : Gaya Politik Baru Kaum Muda - Zakaria Habib Al-Ra’zie; Syaid Mirza Shirazi; Ferdi Prayuda (Prosiding Seminar Nasional Ilmu Pendidikan, 2025)
Young people play a very important role in today's political dynamics. In the context of rapid social change and advances in information technology, young people have found new ways to express their opinions and participate in the political process, one of which is through digital activism. Digital activism refers to political involvement carried out by young people by utilizing digital instruments, especially through social media. This research focuses on youth engagement in digital activism and explores the impact of these new movements on social and political change. The methodology used is a qualitative approach by utilizing secondary data from literature studies, while the applied analytical techniques are descriptive and analytical. The results of the study show that there are various forms of digital activism, including online campaigns, petitions, the use of hashtags, and mobilization of movements through social media. Digital activism also has the potential to influence public policy and public perception. However, this movement is also faced with a number of challenges, such as disinformation, propaganda, and technical obstacles such as uneven internet access in various regions. From this research, it is hoped that new insights can be obtained about the dynamics of youth political participation in the digital era, as well as provide recommendations for social activists and policymakers to support the active involvement of the younger generation in the political process.